Current role of percutaneous transhepatic gallbladder aspiration: from palliative to curative management for acute cholecystitis. (1st October 2016) - Komatsu, Shohei; Tsuchida, Shinobu; Tsukamoto, Tadashi; Wakahara, Tomoyuki; Ashitani, Hiroshi; Ueno, Nozomi; Toyokawa, Akihiro; Watanabe, Akihiko; Sugahara, Atsushi; Mukai, Hidekazu
Abstract: Background: The present study assessed conservative management of acute cholecystitis (AC) with a focus on percutaneous transhepatic gallbladder aspiration (PTGBA). Methods: Consecutive 275 patients with AC who underwent PTGBA were reviewed. Patients aged ≥80 years and/or with American Society of Anesthesiologists score III to IV and/or performance status 3 to 4 were defined as high risk. Patients were classified according to duration from symptom onset to first PTGBA: within 3 days (early PTGBA) or over 3 days (late PTGBA). They were also classified according to duration from first PTGBA to surgery: within 30 days (early surgery) or over 30 days (late surgery). Results: A total of 263 patients (95.6%) showed recovery after PTGBA. There were no significant differences in operating time, blood loss, operating procedure, conversion rate to open surgery, postoperative complications, or postoperative hospital stay between the early and late PTGBA groups or between the early and late surgery groups. No significant complications associated with PTGBA or surgery were observed, including in those at high risk. Conclusions: Percutaneous transhepatic gallbladder aspiration can be a useful alternative for most patients with AC, including those at high risk. Elective cholecystectomy can be performed safely regardless of the timing of PTGBA or surgery. Abstract : Komatsu and colleagues evaluated the safety and efficacy of percutaneous transhepatic gallbladder aspiration (PTGBA) in the management of acute cholecystitis. PTGBA is a useful alternative for most patients with acute cholecystitis, including those at high risk, and elective cholecystectomy can be performed safely regardless of the timing of PTGBA or surgery.